Global, regional and national burden of childhood sexual abuse and bullying in adolescents and young adults: a Global Burden of Disease 2021 analysis - Lin, Derong; Yin, Tong; Shi, Zhuangtang; Xie, Xiaohua; Fang, Jingya; Li, Mei; Li, Yue; Luo, Shuxiong; Xue, Aiguo; Liang, Jingrong (Frontiers in Psychiatry, 2025)
ObjectiveChildhood sexual abuse and bullying (CSA/B) undermine adolescent and young-adult health worldwide. We quantified CSA/B-attributable mortality and disability globally across 204 countries and territories (1990–2021), with regional and national disaggregation.MethodsWe analysed the GBD 2021 dataset and applied the comparative risk assessment framework to estimate CSA/B-attributable deaths and disability-adjusted life years (DALYs) by sex, age and Sociodemographic Index (SDI), summarising temporal trends using estimated annual percentage change (EAPC).ResultsCSA/B-related deaths fell from 260 to 187 (–28 %), whereas DALYs rose from 2.54 million to 3.69 million (+45 %). The age-standardised mortality rate declined (EAPC –2.4 %), but the age-standardised DALY rate grew slightly (EAPC +0.5 %). Males carried higher absolute counts, yet females showed steeper DALY growth (+51 % vs +40 %). High-middle and middle-SDI regions achieved the greatest mortality reductions; deaths climbed 103 % and DALY rates 220 % in low-SDI areas. Anxiety accounted for most disability at 15–19 years, whereas depressive and alcohol-use disorders predominated at 20–24 years. Regionally, South Asia led deaths/DALYs, Australasia was lowest; Age-standardised mortality rates (ASMR) peaked in Eastern Europe, age-standardised DALY rates (ASDR) in high-income North America; DALYs rose fastest in Western/Central/Eastern sub-Saharan Africa.ConclusionsFalling mortality alongside expanding disability reveals a widening survivorship gap driven by mental ill-health, particularly among young women in resource-poor settings. Age-specific, gender-responsive violence-prevention and mental-health services are urgently needed to stem the growing DALY burden and advance global AYA wellbeing.